2017
DOI: 10.1101/139402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thoracolumbar intervertebral disc area morphometry in elderly Chinese men and women: radiographic quantifications at baseline and changes at year-4 follow-up

Abstract: Study Design: A population-based radiographic study with longitudinal follow-up.Objective: To develop a quantitative index for lumbar disc space narrowing (DSN) evaluation in elderly subjects; to determine how DSN in the elderly is influenced by osteoporosis and gender. Results: DAIL correlated with semi-quantitative grading, with sensitivity and specificity varying from 87.3% to 96.8% for grade-1 DSN (<30% reduction in disc height), and 92.9 % to 100% for grade-3 DSN (>60% reduction in disc height). The thora… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Gambacciani et al (35) reported after menopause disc space shows a progressive decrease that almost entirely occurs in the first 5 to 10 years since menopause. However, our recent report in a 4-year follow-up study starting from a mean age of 72.5 years shows, there was a greater lateral thoracic and lumbar disc area loss in women than in men (36). That women have faster disc space narrowing than men even 20 years after menopause concurs with previous reports of Wάng et al (16) and de Schepper et al (37).…”
Section: Discussionsupporting
confidence: 85%
“…Gambacciani et al (35) reported after menopause disc space shows a progressive decrease that almost entirely occurs in the first 5 to 10 years since menopause. However, our recent report in a 4-year follow-up study starting from a mean age of 72.5 years shows, there was a greater lateral thoracic and lumbar disc area loss in women than in men (36). That women have faster disc space narrowing than men even 20 years after menopause concurs with previous reports of Wάng et al (16) and de Schepper et al (37).…”
Section: Discussionsupporting
confidence: 85%
“…Another possibility is that a few osteoporotic-looking EPFs might be initially traumatic due to an unreported (forgotten) old injury. However, even such possibility may exist, the cases would be rare in this carefully executed epidemiological study with follow-up data available for potential validation [some data on year 4 follow-up have been analyzed and parts published (37), and some subjects had year-13 follow-up completed and parts already analyzed]. Fragility fractures are fractures that result from mechanical forces that would not ordinarily result in fracture, i.e., low-level (or 'low energy') trauma.…”
Section: Discussionmentioning
confidence: 99%
“…[15] found that MRI T2 mapping imaging technology could not only quantitatively assess the degree of lumbar intervertebral disc degeneration but also reflect the differences in the degenerative degrees of intervertebral discs in different levels through the T2 values of the nucleus pulposus, providing imaging basis for disease diagnosis. Through the clinical research, [16] found that CT and MRI had certain advantages in the clinical diagnosis of lumbar disc herniation, and the combined application of CT and MRI could reduce the rate of missed diagnosis if necessary.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to [14,16,20,21]. The lumbar vertebra is a part of the vertebral column, which is located in the middle of the back and is made up of vertebrae and intervertebral discs.…”
Section: The Structure Of Lumbar Vertebra and The Degenerative Changesmentioning
confidence: 99%